2017
DOI: 10.4102/rw.v8i1.153
|View full text |Cite
|
Sign up to set email alerts
|

Extensive reading in a tertiary reading programme: Students’ accounts of affective and cognitive benefits

Abstract: This article reports on the extensive reading (ER) component of a reading intervention programme to improve first-year students’ reading proficiency. To make the intervention more practical and to accelerate improvement, an ER component was included in the programme. Two groups of first-year students (high-risk and low-risk) were required to read short stories and novels of their choice and to record their affective and cognitive experiences during the reading to submit as a portfolio. In addition, students an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 28 publications
(44 reference statements)
0
21
0
4
Order By: Relevance
“…In these activities, students can choose books according to their abilities of language and minimize the use of a dictionary on those activities (Delfi & Yamat, 2017). Boakye (Boakye, 2017) claims that extensive reading, along with the other kinds of reading, is conducted to help students increase their reading skills and develop their cognitive and affective abilities. The objective of extensive reading is to make students prefer to read in the target language and motivates them to get understandable texts to be read for pleasure (Pretorius & Lephalala, 2012).…”
Section: Extensive Reading In Efl Classroommentioning
confidence: 99%
“…In these activities, students can choose books according to their abilities of language and minimize the use of a dictionary on those activities (Delfi & Yamat, 2017). Boakye (Boakye, 2017) claims that extensive reading, along with the other kinds of reading, is conducted to help students increase their reading skills and develop their cognitive and affective abilities. The objective of extensive reading is to make students prefer to read in the target language and motivates them to get understandable texts to be read for pleasure (Pretorius & Lephalala, 2012).…”
Section: Extensive Reading In Efl Classroommentioning
confidence: 99%
“…In the South African context, there has been little research conducted with FP learners in particular on the effectiveness of ER. Research into ER has mostly focused on the teacher or university students as the unit of analysis (Boakye 2017a(Boakye , 2017bPretorius & Knoetze 2012;Pretorius & Machet 2004). The participants of the mentioned studies can read independently, with limited support from the teacher; therefore, findings from these studies cannot be extrapolated to learners participating in the current study.…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of studies that have reported positive gains through the implementation of an ERP (Boakye 2017b;Clark & Rumbold 2006;Jacobs, Renandya & Bamford 2000;Krashen 2004). Almost every study conducted to investigate the effect of ER on literacy development has reported positively about this approach, despite different methodologies and contexts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies, report that feshmen tends to struggle during their first year in university in terms of keeping up with their reading loads and the difficulity of their tertiary-level reading materials [1], [6], [15]- [17]. This condition occurs because of the students do not pose a good reading habbit and strategies during their secondary level education.…”
Section: Introductionmentioning
confidence: 99%